Effect of activated silica on polymerization mechanism and strength development of MSWI bottom ash alkali-activated mortars. (20th March 2019) - Huang, Guodong; Ji, Yongsheng; Li, Jun; Zhang, Linglei; Liu, Xiangyu; Liu, Benlin
Highlights: Most of the silica in BA is present in inert form. Lack of active silica affects the formation of polymerization products. Enhancement of liquid sodium silicate is obviously better than solid sodium silicate. Abstract: This study investigated the effect of activated silica on both the polymerization mechanism and strength development of municipal solid waste incineration (MSWI) bottom ash alkali-activated mortars, with a specific focus on increasing the silica content by adding either solid or liquid sodium silicate. The results show that such additives increase the content of active silicon and improve the resulting compressive strength of mortars, which is more effectively enhanced by liquid solid sodium silicate addition. However, a significant decline of these effects was found with increased addition of sodium silicate. Solid sodium silicate is difficult to dissolve; therefore, increasing its content not only fails to improve the content of active silicon but also causes precipitation. Using liquid sodium silicate could further improve the content of active silicon; however, excessive addition will result in a large surplus of activated silicon and thus, causing sodium and magadiite precipitation.